Review of the genus Bubaces (Hemiptera: Heteroptera: Rhyparochromidae: Lethaeini) with descriptions of three new species, new distributional records, and key to species - Brailovsky, Harry; Barrera, Ernesto (Zootaxa, 2020)
The genus Bubaces Distant, 1893 is reviewed and three new species are described: B. gloriosus sp. nov., from Costa Rica (Puntarenas Province) and Mexico (Campeche, Chiapas, Guerrero, Oaxaca, and Veracruz), B. occidentalis sp. nov., from Mexico (Colima, Guerrero, Jalisco, and Michoacan) and B. rostralis sp. nov., from Mexico (Quintana Roo). Additional state faunistic records of the previously described species B. castaneus, B. convergens, B. enatus and B. uhleri are provided. Photographs of the dorsal habitus, the male genital capsule, and the parameres are included, as well as close up photos of the metathoracic scent glands of both sexes. A key to species of the genus is provided.